Automotive bottom structure composite materials selection: digital logic and knowledge based system approach - Maleque, Md. Abdul; Afdzaluddin, Atiqah; Faizul, M.; Sapuan, S. M. (Universiti Putra Malaysia Press, 2014)
A sustainable car means an environmentally friendly, lightweight, affordable, car satisfying all current and future legislations on safety, recyclability and emissions. Hence, the best method to satisfy the above purpose objective is to develop an advanced methodology of lightweight design approach. This methodology can be based on optimal material selection with respect to minimum weight. In addition, if materials selection is included in the procedure, then new types of structural materials can be considered as candidates to be used for car components. For instance, renewable or partly renewable materials like composites containing natural fibers and or natural matrix.